Reversal of carbonate-silicate cation exchange in cold slabs in Earth’s lower mantle - Mingda Lv (Nature Portfolio, 2021)
CaCO3 is more stable than MgCO3 under conditions of Earth’s lowermost mantle, with implications for deep mantle chemistry.